State governance and public finance theory : a Chinese perspective - Ma, Jun, 1964-; Gao, Peiyong (Routledge, 2025)
"This book explores the fundamental theories, methodologies and innovative directions of public finance research, focusing on its relationship with and role in state governance. Public finance is the foundation and an important pillar of state governance. The two mutually reinforce each other at the macro level and in broader contexts, necessitating the reconstruction of a public finance discipline system that meets the needs of Chinese society. This book addresses key theoretical issues in public finance, with its main discussions covering: (1) the need, feasibility and direction of innovation in basic theory; (2) research approaches; (3) a multidisciplinary perspective; (4) the history, progress and future of public finance in China; (5) the development of the discipline and teaching approaches; (6) research trends; (7) quantitative research methods; and (8) practical issues related to tax system reform. The title will be a valuable reference for researchers and students in the fields of public economics, public finance, Chinese fiscal policy and tax system"-- Provided by publisher.
"First published in English 2025. Translated by Ye Shuang. English Version by permission of China Social Sciences Press."
Keywords: Finance, Public -- China.; elektronické knihy; electronic books